Report on recent results obtained in TCABR. (March 2015) - Galvão, R M O; Amador, C H S; Baquero, W A H; Borges, F; Caldas, I L; Cuevas, N A M; Duarte, V N; Elfimov, A G; Elizondo, J I; Fonseca, A M M; Germano, T M; Grenfell, G G; et al.
Abstract: Recent results of experimental work and theoretical modeling carried out in the TCABR tokamak are reported on characterization of MHD instabilities, improved diagnostics of rotation of the plasma column, excitation of Alven global modes, identification of GAMs, and the effect of rotation on their behavior. Detailed measurements of edge electrostatic perturbations and of magnetic island evolution and rotation indicate that the edge turbulence is substantially affected by the islands growth, leading to a strong modulation of the edge particle losses at the same frequency of the MHD activity. Measurements with spatial resolution also show that the growth of the MHD activity is due to nonlinear coupling of magnetic islands with different poloidal mode numbers, which increases the impurity influx. A new system of data acquisition and processing of the TCABR plasma rotation diagnostic was implemented. The system is based upon a single monochromator coupled with six photomultipliers tubes and allows one toroidal and two poloidal simultaneous rotation measurements. The excitation of Global Alfven Waves - GAW has been investigated, using a new type of radio frequency amplifier. The GAW resonances are searched either by a pre-programmed density variation, at fixed generator frequency, or through three RF frequency sweeps from 2 to 4.5 MHz, at stationary density. GAW resonances have been found and their somewhat new characteristics are presented. The investigation of the effect of poloidal and toroidal rotation on the characteristics of the geodesic acoustic mode has been investigated, both theoretically and experimentally. It is found that the assumption of isothermal flux surfaces gives rise to a third branch of this mode. Detailed predictions coupled with experimental measurements are currently being carried out to investigate this question.